The association of mandibular third molar impaction with the dental and periodontal lesions in the adjacent second molars. Issue 10 (23rd February 2021) - Tai, Shanshan; Zhou, Yang; Pathak, Janak L.; Piao, Zhengguo; Zhou, Libin
Abstract: Background: It is a consensus that symptomatic impacted mandibular third molars (MTMs) need to be removed. Although the prophylactic extraction of asymptomatic impacted MTMs remains controversial. This study aims to investigate the effects of MTMs on themselves and adjacent teeth pathophysiology and provide the evidence for prophylactic extraction of impacted MTMs. Methods: A retrospective study of panoramic radiographs of patients visited the Affiliated Stomatology Hospital of Guangzhou Medical University from April 2014 to May 2018 was conducted to investigate the dental and periodontal lesions in MTMs and adjacent mandibular second molars (MSMs), as well as the correlation of tooth lesion severity with patient age. Results: Among the 2650 impacted MTMs, 6.98% dental lesions and 37.81% periodontal lesions were found, as well as 24.63% dental lesions and 35.30% periodontal lesions in the distal of adjacent MSMs. 9.27%, 2.02%, 0.47%, and 13.33% dental lesions and 48.81%, 17.31%, 5.19%, and 10% periodontal lesions were observed in MTMs with mesioangular, horizontal, inverted and distoangular impaction types, respectively. For the adjacent MSMs, 31.98%, 11.82%, 1.94%, and 13.33% distal dental lesions and 45.74%, 16.95%, 2.91%, and 23.33% distal periodontal lesions were found in mesioangular, horizontal, inverted and distoangular impaction types, respectively. In mesioangular MTMs, the severity of the distal dental and periodontal lesions in the adjacent MSMs showed a high‐positive correlation with patient age ( P  < 0.05) Conclusion: Early prophylactic extraction of MTMs with mesioangular‐impaction and close monitoring of MTMs with horizontal/inverted‐impaction could prevent impacted MTMs‐associated lesions in MTMs/MSMs.